RELACJE MIĘDZY „AGENCJĄ PRACY CZASOWEJ” I PRZED SIĘBIORCĄ-UŻYTKOWNIKIEM WE FRANCJI - Makowski, Dariusz (Wydział Prawa i Administracji UAM, 2001)
It comes out of the definition of temporary employment agency that it is a natural or legal person (i.e. - an individual or a corporation) the activity of which consists exclusively in employing extemporaneously (as the occasion arises) some workers to perform some concrete job on behalf of an entrepreneur (article L. 124-1 of the French Labour Code). A legal link between such an agency and an entrepreneur-holder is established as a result of passing a contract on committing a temporary worker to the disposal of the entrepreneur (in French: contract de mise à disposition). The Author discusses the contents and a form of a contract on committing a worker, next - obligations of both parts to such a contract and their responsibility in case of non-performing them or in case of damages caused under the period of validity of this contract. Also legal character of this type of a contract is discussed by the Author.
RELATIONS BETWEEN A TEMPORARY EMPLOYMENT AGENCY AND AN ENTREPRENEUR-HOLDER IN FRANCE